Innate epithelial and functional differences in airway epithelium of children with acute wheeze - Looi, Kevin; Iosifidis, Thomas; Harrison, Saraya; Stick, Stephen M.; LeSouef, Peter; Laing, Ingrid A.; Kicic, Anthony (Frontiers in Cell and Developmental Biology, 2025)
BackgroundEarly childhood wheeze is a major risk factor for asthma. However, not all children who wheeze will develop the disease. The airway epithelium has been shown to be involved in asthma pathogenesis. Despite this, the airway epithelium of children with acute wheeze remains poorly characterized.MethodsUpper airway epithelial cells (AEC) from children with acute wheeze and non-wheeze controls were cultured and expanded. Markers of epithelial lineage (Cytokeratin (KRT)-5, −19) and vimentin were assessed via qPCR and immunocytochemistry. Inflammatory cytokines (Interleukin (IL)-1β, −6, and −8) were measured using ELISA. Tight junction (TJ) protein expression and barrier integrity were determined via In-Cell Western and paracellular permeability assays, respectively.ResultsUpper AECs from children with acute wheeze had significantly higher KRT19 and lower vimentin gene expression compared to non-wheeze controls but similar KRT5 levels. Similar staining intensities of KRT5 and KRT19 proteins were observed in both cohorts. IL-6 and IL-8 levels were not significantly different, but IL-1β was increased in cultures from children with acute wheeze compared to controls. Tight junction protein expression of claudin-1, occludin and ZO-1 were significantly lower in acute wheeze cohorts, concomitant with increased paracellular permeability.ConclusionAirway epithelium of children experiencing acute wheeze appears abnormal, primarily with compromised epithelial barrier integrity.